Substitution of Red Amaranth Flour (Amaranthus Tricolor L.) in Manufacture Wet Noodles as Foods High in Iron (Fe) - Putri, Hikmathine Osella; Arrazy, Syafran; Wahyudi, Wahyudi (GLOBAL HEALTH SCIENCE GROUP, 2024)
Wet noodles with the addition of Amaranthus tricolor L can be used well as an alternative food source of iron. Amaranthus tricolor L has a high iron content and has the potential to prevent anemia. The aim of this research was to determine the acceptability of wet noodles made from high iron Amaranthus tricolor L flour with the addition of high protein wheat flour and mocaf flour. This research method is experimental research using a Completely Randomized Design (CRD) using 3 treatments. Treatment consisted of adding 0%, 25% and 50% Amaranthus tricolor L. Statistical analysis of data was carried out with SPSS using one-way ANOVA and Duncan's test. The research was carried out in three ways, namely the product development stage, acceptability test and iron content test. Hedonic test data from research on the substitution of Amaranthus tricolor L flour in making wet noodles with 25 untrained panelists, namely students from the Faculty of Public Health, UIN North Sumatra. The test results for the acceptability of processed wet noodles based on the assessment of color, aroma and taste were preferred more by the panelists, namely F1 (Control) without the addition of Amaranthus tricolor L with average results of color of (4.36), aroma of (3.92), taste of (4.48) and texture (4.08). The results of research on Fe levels in wet noodles with the addition of Amaranthus tricolor L which has the highest Fe levels is the addition of 50% red spinach, namely 227 mg/kg (F3) rather than (F2) which is 18.4 mg/kg.